Case Report: Jejunoileal Atresia With Persistent Poor Bowel Function Can Occur After Surgical Correction for Hirschsprung Disease - AlBassam, Bassam N.; Al-Shammari, Ahmad A.; AlQahtani, Saleh A.; Hassan, Elham (Frontiers in Pediatrics, 2022)
Jejunoileal atresia (JIA) is one of the common etiologies of intestinal obtrusion in neonates. However, cases of concomitant ileal atresia and Hirschsprung disease rarely occur. We report the case of a male infant who had JIA concomitantly with Hirschsprung disease that was re-anastomosed. The patient underwent an exploratory laparotomy to resect the dilated terminal ileum. Subsequently, owing to a significantly dilated proximal bowel, he underwent a second exploratory laparotomy. However, he continued to have feeding intolerance postoperatively. He had colonic aganglionosis and was diagnosed with Hirschsprung disease. A third laparotomy was then performed. Additionally, he had recurrent episodes of gram-negative bacteremia, especially candida parapsilosis fungemia, despite receiving antibiotics and antifungal, and there were no identifiable underlying genetic or immunological causes. Finally, the patient had recurrent episodes of hypoglycemia, central hypothyroidism, and multiple organ failure and died at the age of 7 months. The concomitant ileal atresia and Hirschsprung disease was thought to be due to a common intrauterine vascular accident, together with loss of bowel, thereby acting as a barrier for the caudal migration of neuromeric cells and leading to colonic aganglionosis. In this case, ileal atresia was associated with colonic aganglionosis, central hypothyroidism, and persistent bacteremia, which is a unique finding. In cases of JIA, persistent poor bowel function after surgical correction of concomitant Hirschsprung disease should be considered.